Multiple H2 occupancy of cages of clathrate hydrate under mild condition - Lu, Hailong; Wang, Jianwei; Liu, Changling; Ratcliffe, Christopher I.; Becker, Udo; Kumar, Rajnish; Ripmeester, John A. (Journal of the American Chemical Society, 2012)
Experiments were carried out by reacting H(2) gas with N(2) hydrate at a temperature of 243 K and a pressure of 15 MPa. The characterizations of the reaction products indicated that multiple H(2) molecules can be loaded into both large and small cages of structure II clathrate hydrates. The realization of multiple H(2) occupancy of hydrate cages under moderate conditions not only brings new insights into hydrogen clathrates but also refreshes the perspective of clathrate hydrates as hydrogen storage media.

Low-pressure synthesis and characterization of hydrogen-filled ice ic - Kumar, Rajnish; Klug, Dennis D.; Ratcliffe, Christopher I.; Tulk, Christopher A.; Ripmeester, John A. (Angewandte Chemie-International Edition, 2013)
Keywords: Clathrates; cubic ice; hydrates; Hydrogen